Just haven't met you yet - Cousens, Sophie (G. P. Putnam's Sons, 2021)
"From the New York Times bestselling author of This Time Next Year comes a heartwarming and hilarious tale that asks: What if you picked up the wrong suitcase and fell head over heels for its mystery owner?"--